Role of hydrophobic residues for the gaseous formation of helical motifs. Issue 35 (12th April 2019) - Liu, Lin; Dong, Xin; Liu, Yichang; Österlund, Nicklas; Gräslund, Astrid; Carloni, Paolo; Li, Jinyu
Abstract : The secondary structure content of proteins and their complexes may change significantly on passing from aqueous solution to the gas phase (as in mass spectrometry experiments). Abstract : The secondary structure content of proteins and their complexes may change significantly on passing from aqueous solution to the gas phase (as in mass spectrometry experiments). In this work, we investigate the impact of hydrophobic residues on the formation of the secondary structure of a real protein complex in the gas phase. We focus on a well-studied protein complex, the amyloid-β (1-40) dimer (2Aβ). Molecular dynamics simulations reproduce the results of ion mobility-mass spectrometry experiments. In addition, a helix (not present in the solution) is identified involving 19 FFAED 23, consistent with infrared spectroscopy data on an Aβ segment. Our simulations further point to the role of hydrophobic residues in the formation of helical motifs – hydrophobic sidechains "shield" helices from being approached by residues that carry hydrogen bond sites. In particular, two hydrophobic phenylalanine residues, F19 and F20, play an important role for the helix, which is induced in the gas phase in spite of the presence of two carboxyl-containing residues.